2015
DOI: 10.1016/j.surg.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol decreases nitric oxide production by hepatocytes during inflammation

Abstract: Introduction The production of excessive amounts of nitric oxide (NO) through inducible nitric oxide synthase (iNOS) contributes to organ injury, inflammation, and mortality after shock. Resveratrol (RSV) is a natural polyphenol that decreases shock-induced hepatic injury and inflammation. We hypothesized that RSV would mediate these effects by reducing hepatocyte iNOS production. Methods Rat hepatocytes were isolated, cultured with varying concentrations of RSV, and then stimulated to induce iNOS with inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
2
12
1
Order By: Relevance
“…Resveratrol was also found to reduce NO production and iNOS expression through the blockade of IκBα/NF‐κB signaling pathway in lipopolysaccharide‐induced RAW 264.7 cells . Similarly, the induction of NF‐κB‐mediated NO generation as well as iNOS expression in hepatocytes during inflammation was suppressed in the presence of resveratrol (Fig. ).…”
Section: Indirect Antioxidant Defense Mechanisms Of Resveratrolmentioning
confidence: 78%
“…Resveratrol was also found to reduce NO production and iNOS expression through the blockade of IκBα/NF‐κB signaling pathway in lipopolysaccharide‐induced RAW 264.7 cells . Similarly, the induction of NF‐κB‐mediated NO generation as well as iNOS expression in hepatocytes during inflammation was suppressed in the presence of resveratrol (Fig. ).…”
Section: Indirect Antioxidant Defense Mechanisms Of Resveratrolmentioning
confidence: 78%
“…RSV, a polyphenolic compound found in red wine, has various health beneficial effects through JNK/NF-κB, p38, NO/NOS pathway [ 31 , 32 ]. Li et al [ 33 ] found that RSV can improve renal interstitial fibrosis by specifically inhibiting Smad3 acetylation in unilateral ureteral obstruction mice.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the production of excessive amounts of nitric oxide (NO) contributes to inflammation and tissue injury [33]. Regarding this rational, we hypothesized that RSV and omega-3 fatty acids can ameliorate wound healing due to an anti-inflammatory effect by inhibition of NO production, an effect that has been reported in previous studies [34,35]. NLCs presented a NO production inhibition of 64.14 ± 2.08% demonstrating an effect of approximate magnitude of phenylethanoids (NO production inhibition of 6.3-62.3%) that for the extent of NO production inhibition were reported to possess anti-inflammatory properties [36].…”
Section: In Vitro Cellular Evaluation Of Anti-inflammatory Effectmentioning
confidence: 85%